Correlation of Lumbar Spine MRI Signal Alterations with DEXA-derived Bone Mineral Density and T-scores: A Cross-sectional Analytical Study - Amit Sarma; Mrinal Kanti Singha (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Osteoporosis is a systemic skeletal disorder that increases the risk of fragility fracture and constitutes a major global health burden. Dual-Energy X-Ray Absorptiometry (DEXA) is the clinical reference standard for Bone Mineral Density (BMD) assessment but, as a two-dimensional projection technique, does not directly evaluate trabecular microarchitecture or marrow composition. Magnetic Resonance Imaging (MRI) signal characteristics of vertebral marrow have been proposed as opportunistic markers of Vertebral Bone Quality (VBQ). Aim: To evaluate the correlation between lumbar spine MRI signal alterations (T1- and T2-weighted) and DEXA-derived BMD parameters, including BMD, T-score and Z-score, in patients undergoing lumbar spine imaging. Materials and Methods: A cross-sectional analytical study was conducted at Assam Down Town University, Guwahati, Assam, India, from October 2023 to April 2024. A total of 100 adults of either sex who underwent both lumbar spine MRI (1.5 Tesla) and DEXA were evaluated. A circular Region Of Interest (ROI) of 1 cm² was placed in the central trabecular portion of the L3 vertebral body on T1- and T2- weighted sagittal images, avoiding cortical bone, end-plate changes and focal lesions. DEXA-derived BMD was classified according to World Health Organisation (WHO) T-score criteria. Pearson’s correlation coefficient with 95% Confidence Intervals (CI) was used to assess associations; a two-tailed p-value